PERANCANGAN SIMPLE DESIGN SYSTEM CANVAS SEBAGAI PEDOMAN ANTARMUKA PENGGUNA UNTUK STARTUP INDONESIA - Mochammad Faizal (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2021)
Industry 4.0 era can be felt by the growing number of startups in Indonesia. The majority of startups in Indonesia that are still in micro-scale often found problems related to funding and human resources. In addition, all startups in Indonesia have used websites and mobile applications to support their business activities. This research aims to assist startups in formulating a simple design system, as a guideline for the media they are designing. This article will describe the linear design strategy by conducting a literature review, visual observation, interviews, and taxonomic analysis to collect and analyze the data needed. This study found three visual elements with 11 parts that are fundamental to a simple design system. The researcher has designed a working canvas called